Sequential transcriptome profiling: comparative analysis of normal and canine lymphoma preceding detailed T-cell and B-cell subtype comparison - Kim, Yeji; Kim, Jihyun; Song, Yunji; Jang, Keunhwan; Kim, Se Eun; Kim, Ha-Jung (Frontiers in Veterinary Science, 2025)
IntroductionAs the lifespan of companion animals extends, the incidence of tumor also increases. Among these tumors, lymphoma is reported as the most prevalent hematopoietic tumor with a 80-90% prevalence rate. Ongoing research spans multiple domains, aiming to uncover novel therapeutic targets, including small molecular weight inhibitors, antibody treatments, and subtype-specific selective agents.MethodsTranscriptional profiling was performed on canine lymphoma samples to identify genes and functional pathways associated with pathogenesis, treatment response, and prognosis. Additionally, genes with potential relevance to the clinical characteristics of T-cell lymphoma (TCL), which is characterized by a low treatment response and poor prognosis, were identified through a comparative analysis of different lymphoma subtypes.ResultsWithin the canine lymphoma group, HERC5 showed consistent upregulation, a gene similarly implicated in human acute myeloid leukemia but previously no reports exist. Additionally, noteworthy genes, including IKZF2, CCL4, SAA1, and CD40, exhibited differential expression in the TCL group compared to the B-cell lymphoma (BCL) group.DiscussionThe upregulation of HERC5 may impact on canine lymphoma pathogenicity. Furthermore, the upregulation of IKZF2, CCL4, and SAA1, along with the downregulation of CD40, may contribute to adverse clinical characteristics of TCL in dogs.